Dziecko z mukopolisacharydozą w przedszkolu – perspektywa terapeutów - Kamyk-Wawryszuk, Agnieszka (Studia Edukacyjne, 2018)
Mucopolysaccharidosis (MPS) is a rare and progressive disorder. It gradually causes the disappearance of the child’s learned skills. There are few scientificpapers concerning the rules of conduct with a child of preschool age with MPS, and therefore therapists’ work often comes down to searching for adequate methods of therapy in order to preserve the skills acquired by the pre-schooler as long as possible. The main research question was: “How does the treatment of a child with mucopolysaccharidosis at an Inclusive Preschool look like from the perspective of therapists?” Four therapists working with two boys suffering from MPS were surveyed in the study.